On the coupling of self-conjugate systems with SL(3,R) symmetry - Castilho Alcarás, J. A.; Biedenharn, L. C. (AIP Publishing, 1978)
The coupling of unitary self-conjugate SL(3,R) multiplicity-free irreps is explicitly calculated. It is proven that pair-wise coupling of a finite number of these self-conjugate irreps never contains a continuum SL(3,R) irrep which is multiplicity-free. The significance of SL(3,R) symmetry in nuclear and hadronic systems is discussed, including implications for the coupling of quarkels. © 1979 American Institute of Physics.